2004
DOI: 10.1093/ndt/gfh313
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ghrelin levels in patients undergoing haemodialysis and peritoneal dialysis

Abstract: PGhr levels were moderately and similarly increased in patients undergoing HD and PD. Age was a strong determinant of PGhr levels, both in uraemic patients and in healthy controls. Dialysis adequacy, residual renal function and inflammation did not appear to influence ghrelin levels in these patients. The negative correlation between PGhr and nutritional markers suggests that low dietary intake causes increases in ghrelin secretion in dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
5
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 20 publications
10
72
5
1
Order By: Relevance
“…We demonstrated elevated endogenous total ghrelin levels in this cohort of PD patients, compared with BMI-matched healthy individuals, in agreement with observations by Perez-Fontan et al (29) and Ayala et al (30). Although there are high endogenous levels of total ghrelin, dietary energy intake is paradoxically reduced in PD patients.…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated elevated endogenous total ghrelin levels in this cohort of PD patients, compared with BMI-matched healthy individuals, in agreement with observations by Perez-Fontan et al (29) and Ayala et al (30). Although there are high endogenous levels of total ghrelin, dietary energy intake is paradoxically reduced in PD patients.…”
Section: Discussionsupporting
confidence: 93%
“…Increased total ghrelin has been reported to be associated with cachexia in chronic heart failure patients (Nagaya et al 2001). Increased total ghrelin levels are also reported in dialysis patients (Perez-Fontan et al 2004). There are two major forms of ghrelin-acylated and des-acylated.…”
Section: Discussionmentioning
confidence: 98%
“…Although ghrelin is degraded in the kidney, its levels are not uniformly increased in CKD patients [15]. Some studies with dialysis patients have demonstrated elevated ghrelin levels, whereas other studies have shown normal or even low ghrelin levels in CKD patients [16,17]. A possible explanation for these seemingly contradicting findings is that only UAG levels were elevated in the CKD patients.…”
Section: Ghrelin Obestatin and Ckdmentioning
confidence: 99%